2013 IEEE/RSJ International Conference on Intelligent Robots and Systems 2013
DOI: 10.1109/iros.2013.6696752
|View full text |Cite
|
Sign up to set email alerts
|

Interactive object classification using sensorimotor contingencies

Abstract: Abstract-Understanding and representing objects and their function is a challenging task. Objects we manipulate in our daily activities can be described and categorized in various ways according to their properties or affordances, depending also on our perception of those. In this work, we are interested in representing the knowledge acquired through interaction with objects, describing these in terms of action-effect relations, i.e. sensorimotor contingencies, rather than static shape or appearance representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…More recently, the area of interactive perception goes beyond the mere selection of percepts toward actively changing the state of the environment to increase information gain. In studies on robot vision, it has been shown that a visual scene can be disambiguated by actively manipulating objects in the scene through a robotic arm (Fitzpatrick and Metta 2002;Björkman et al 2013;Högman et al 2013). Similar implications apply to other sensory modalities.…”
Section: Action In Robotic Perceptionmentioning
confidence: 92%
“…More recently, the area of interactive perception goes beyond the mere selection of percepts toward actively changing the state of the environment to increase information gain. In studies on robot vision, it has been shown that a visual scene can be disambiguated by actively manipulating objects in the scene through a robotic arm (Fitzpatrick and Metta 2002;Björkman et al 2013;Högman et al 2013). Similar implications apply to other sensory modalities.…”
Section: Action In Robotic Perceptionmentioning
confidence: 92%
“…We believe that such questions can not always be resolved from single images alone and are exploring methods for active object hypothesis testing and validation [75]. We also use the presented system to learn more about objects through tactile exploration of object shape [76] and study objects in terms of object-related sensorimotor contingencies [77].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that sensory information is always measured with respect to an object reference, as done in [30], we reformulate the function (2) as follows:…”
Section: A Action-effect As Forward Modelmentioning
confidence: 99%
“…In the experiments we kept the height fixed to positions along the lower part of the object, such as the objects do not fall, and applied actions in directions parallel to the support where the object is placed. The velocity a V extends the dimensionality of the action space previously defined by a = (a X ) in [30]. Some object properties such as rolling for the balls, are only "triggered" from a given velocity.…”
Section: A Model For Pushingmentioning
confidence: 99%
See 1 more Smart Citation